Visceral Leishmaniasis in Children in Southern Turkey: Evaluation of Clinical and Laboratory Findings and Liposomal Amphotericin B Treatment - Barbaros Şahin Karagün; Özlem Özgür; İlgen Şaşmaz; Bülent Antmen; Emine Kocabaş; Emre Alhan (Galenos Yayinevi, 2019)
Aim:Visceral leishmaniasis (VL) is a systemic infection that spreads hematogenously and affects the reticuloendothelial system by the infection of macrophages. VL occurs commonly in children, and only rarely in adults. VL should be considered in patients with prolonged high fever, hepatosplenomegaly, pancytopenia, weight loss, pallor and hypergammaglobulinemia.Materials and Methods:In this study, a total of 18 pediatric patients -9 (50%) males and 9 (50%) females- treated for VL at our clinic from January 2004 to July 2014 were analyzed retrospectively. Average time from symptom onset to hospital admission was 64±21 days (range: 30-100 days). The mean age of patients was 88±40 months (range: 36-182 months). Results:The most common symptom at presentation was fever (88.9%). Other common symptoms were fatigue, chills, weight loss and anorexia. Physical examination revealed splenomegaly and hepatomegaly in all patients. Anemia (92.4%), leukopenia (78.7%) and thrombocytopenia (76.2%) were the most prominent laboratory abnormalities and 82.2% of the patients were pancytopenic on admission. Bone marrow smear was positive for leishmania in 100% of the patients. All patients received treatment with liposomal amphotericin B.Conclusion:In certain regions, increased humidity rates associated with construction of dams and irrigation canals may lead to changes in the ecological balance and thus cause an increase in the population of disease-spreading vectors. Additionally, recent migration from the middle-eastern region to western parts of the world due to regional civil wars may have contributed to the observed increase in the incidence of various diseases such as VL.